Preparation and characterization of a chitosan/MgO composite for the effective removal of reactive blue 19 dye from aqueous solution - Nga, Nguyen Kim; Thuy Chau, Nguyen Thi; Viet, Pham Hung (Journal of science. Advanced materials and devices, 2020)
We developed a multi-functional adsorbent with excellent adsorption capacity and low contact time for reactive blue (RB) 19 dye removal. A multi-functional film based on chitosan (CS) combined with nanosized MgO was prepared by solvent casting with mild drying. The CS/MgO composite product was characterized by Fourier transform infrared spectroscopy, X-ray diffractometry, Field emission-scanning microscopy, and thermal gravimetric and differential thermal analyses. The adsorption properties of the CS/MgO film for RB 19 removal, including effects of key factors (i.e., adsorbent dosage, contact time, pH, initial dye concentration), adsorption equilibrium, and adsorption kinetics, were then investigated. Results showed that the adsorption performance of the CS/MgO film for RB 19 removal was strongly dependent on these factors. The optimal contact time for RB 19 removal by the CS/MgO film was 120 min, which is shorter than that required by other CS adsorbents. Moreover, the maximum adsorption capacities of the adsorbent were generally high (408.16, 485.43, and 512.82 mg·g−1 at 18, 28, and 38 °C, respectively). The equilibrium adsorption data could be best described by the Langmuir isotherm model, and the adsorption kinetics followed a pseudo second-order reaction. Thermodynamic parameters, such as changes in free energy (ΔG°), enthalpy (ΔH°), and entropy (ΔS°), indicated that adsorption by the CS/MgO film was spontaneous and endothermic.